LITERATURE REVIEW : HUBUNGAN SELF DISCLOSURE DENGAN FENOMENA HYPERHONEST PADA REMAJA - Pratiwi, Utari; Firman; Netrawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The influence of adolescent self-disclosure in the context of social media use, especially related to the hyperhonest phenomenon. Self-disclosure on social media allows teenagers to reveal personal information intensively, which can influence the formation of their identity and social relationships. This research uses a literature study approach to compile and analyze various relevant literature sources regarding adolescent self-disclosure and the hyperhonest phenomenon on social media. The selected literature sources include journal articles, books, and dissertations that examine this topic from various perspectives. Teenagers' elf-disclosure in social media provides a platform that allows them to develop their self-identity in a broader and deeper way. Features like “Close Friends” on Instagram influence the intensity of self-disclosure by creating a more restricted and intimate environment. However, uncontrolled use of self-disclosure can also pose risks to teenagers' privacy and mental health. Adolescents' self-disclosure on social media plays an important role in shaping their identity and social relationships. By disclosing personal information online, teens can construct narratives about themselves and strengthen social bonds with their peers. However, it is important to pay attention to wise privacy management and awareness of the psychological impact of intensive self-disclosure.